Development of Dual-Core Spun Yarn Using Different Filaments as a Core and its Impact on Denim Fabric Properties - Ahsan Habib; Yağmur Olgun; Osman Babaarslan (Textile & Leather Review, 2024)
Consumer preferences for comfortable and well-fitting clothing have led to an increased demand for yarns (elastic) in denim fabric production. The study focuses on the manufacture of yarns (dual core) with various core components including T400® (Polyethylene terephthalate) / poly trimethylene terephthalate), PBT (Polybutylene terephthalate), Polyester (PES), and elastane (Lycra®) and their impact on denim fabric properties. The study involves the production of Ne 18/1 yarns (dual core) using an adjusted spinning method (ring) with elastane and different filaments in the core and additionally, twill (3/1 ‘Z’) fabric (denim) is manufactured using those yarns, and then fabric and yarn characteristics are evaluated. The results show significant variations in fabric and yarn characteristics based on the type of core material used. The yarn properties, such as the neps (+200), strength, thin place (-50), hairiness, elongation %, unevenness %, and thick place (+50) of yarns (dual core) are affected by the selection of filament. Fabric properties like weight, elasticity %, strength (tensile), strength (tearing), shrinkage %, and stiffness exhibit differences depending on the core filament. The statistical analysis employs one-way ANOVA to investigate the significance of differences in yarn and fabric properties within various core materials. The outcomes of this experimental work contribute valuable understandings of the production of yarns (dual core) with several filaments for enhancing fabric (denim) performance.